Struggle for peace - "Galtung, Johan" (Ahmedabad, 1984)
This book covers the following topics: The western cultural tradition and the struggle for peace; world conflict formation processes in the 1980; Disarmament: Nato and the states of western Europe : the search for an alternative strategy etc.
Keywords: Peack struggle